REPERCUSSÃO DA IMPLANTAÇÃO DA AUDITORIA CONCORRENTE DE ENFERMAGEM INTRA HOSPITALAR - Trevisan, Rúbia O. S.; Correia, Carina; Vianna, Carla D.; Bragas, Luciane Z. T. d. (Salão do Conhecimento, 2013)
Resumo